Differences in Factors Associated with Depressive Symptoms between Urban and Rural Female Adolescents in Korea - Lee, Gyuyoung; Ham, Ok Kyung; Lee, Bo Gyeong; Kim, Abuan Micah (Journal of Korean Academy of Nursing, 2018)
To examine the prevalence of depressive symptoms and differentiate factors associated with them in urban and rural areas by applying the Ecological Models of Health Behavior. We employed a cross-sectional design and convenience sample of 460 female adolescents. The instruments included the Adolescent Mental-Health Problem-Behavior Questionnaire (AMPQ-II) and the Beck Depression Inventory (BDI). Depressive symptoms were confirmed in 15.7% of urban adolescents and 22.9% of rural adolescents ( <.05). In the urban group, perception of health and stress associated with school performance were significantly associated with depressive symptoms. In the rural group, academic/internet related problems and rule violations were significantly associated with depressive symptoms ( <.05). General life happiness, worry/anxiety, and mood/suicidal ideation were common factors in both urban and rural areas ( <.05). Multiple factors were associated with depressive symptoms, and those significant factors differed between urban and rural female youths. Accordingly, tailored approaches are required considering urban and rural differences. The approaches should include intrapersonal, interpersonal, and organizational levels of interventions.